THE INCOME TAX–STATISTICAL ASPECTS. - White, Edward (The Accounting Review, 1928)
Abstract The attendant of income tax legislation is the presentation of statistics of profits and losses; and to the U.S. Congress, framing the Revenue Act of 1916, it became apparent that accurate information regarding the distribution of income in the U.S. has been a necessity. Accordingly, a provision requiring the preparation of statistics with respect to the operation of the income tax law has been incorporated in the act, considering statistics covering classification of taxpayers and of income, amounts allowed as deductions and exemptions, and other facts deemed pertinent and valuable. Accordingly, statistical reports have inaugurated an epoch in income statistics in the U.S. These data hold different significance for different classes of people. To the accountant most interesting tables are those showing for both individuals and corporations, receipts and disbursements by sources of income and nature of deduction. Similarly, to the sales manager, the most important data comprise tables showing the distribution of individual returns by size of net income for each state.